Program Majalah Dinding Komunikasi Ceria Sebagai Media Informasi Sekolah Dalam Mengajarkan Komunikasi Positif - Kuncoro, Fringki Eko; Rizki, Muhammad; Armasito, Armasito (Jurnal Aksi Dosen dan Mahasiswa, 2025)
This study aims to explore the implementation of the "Komunikas Ceria" Wall Magazine Program as a school information medium for teaching positive communication to students at SD Negeri 14 Indralaya. The method used was descriptive qualitative research, with data collected through interviews, observations, and documentation throughout the program's implementation. The results showed that the program was effective in improving students' communication skills, as evidenced by their increased active participation in class discussions and their confidence in expressing ideas and opinions. Previously quieter students began to demonstrate greater self-confidence, while positive changes were also noted in social interactions between students. However, several challenges remain, particularly related to learning motivation, which still needs to be improved. This study concluded that the program's success depends not only on the implementation of learning techniques but also requires continuous support from parents and the school. It is recommended to continue this positive communication program with deeper integration into the curriculum and involving various stakeholders to enhance its comprehensive impact on students' socio-emotional development. Further research using mixed methods is also recommended to gain a more comprehensive understanding of the program's effectiveness